2016
DOI: 10.1007/s00210-016-1212-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with the anti-parasitic drug diminazene aceturate on antioxidant enzymes in rat liver and kidney

Abstract: Diminazene aceturate (DA) is the active component of some trypanocidal drugs used for the treatment of animals infected with trypanosomosis and babesiosis. Residues of DA may cause hepatotoxic and nephrotoxic effects. Therefore, the purpose of this study was to investigate the occurrence of oxidative stress, i.e., changes in the antioxidant defense system of rats treated with a single dose of 3.5 mg kg(-1) of DA. All treatments were intramuscularly administered, and evaluations were performed on days 7 and 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…For example, Baldissera et al reported an increase in liver and renal oxidative stress and a reduction in anti-oxidant enzymes (catalase, SOD) following a 21-day treatment with 3.5 mg/kg of DIZE. [34] The study also documented histological damage to the kidney and liver byday 21 of treatment. At 10 mg/kg, it was reported to cause GI and respiratory issues in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baldissera et al reported an increase in liver and renal oxidative stress and a reduction in anti-oxidant enzymes (catalase, SOD) following a 21-day treatment with 3.5 mg/kg of DIZE. [34] The study also documented histological damage to the kidney and liver byday 21 of treatment. At 10 mg/kg, it was reported to cause GI and respiratory issues in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…2007; Vitouley et al 2012) since trypanosomes can hide in the brain. In this sense, formulations with trypanocidal action, such as N-NS (Baldissera et al 2016 a , b ), have the capacity to cross the BBB, and thus eliminate the parasite from the CNS, acting as an important resource to cure the disease. Recently, a study conducted by Oliveira et al .…”
Section: Discussionmentioning
confidence: 99%
“…The injection volume was 20 µ L, and the procedure followed the method described by Baldissera et al . (2016 b ). The sample and mobile phase were filtered through 0·45 µ m membrane filter (Millipore), and degassed by ultrasonic bath prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…They are the mainstay of trypanosomosis control measures (ONYIAH, trypanocidal drugs. They are the mainstay of trypanosomosis control measures (ONYIAH, 1997;BARRETT et al, 2007) and will probably remain so for a long time, in spite of the 1997; BARRETT et al, 2007) and will probably remain so for a long time, in spite of the problems of drug resistance and toxicity (ROSS and TAYLOR, 1990;GEERTS et al, 2001; problems of drug resistance and toxicity (ROSS and TAYLOR, 1990;GEERTS et al, 2001;BALDISSERA et al, 2016a) because drugs are the only method of control readily available BALDISSERA et al, 2016a) because drugs are the only method of control readily available to individual farmers. to individual farmers.…”
Section: Chemotherapy Of Trypanosomosis Chemotherapy Of Trypanosomosismentioning
confidence: 99%